Imaging study of adult coccygeal morphology using direct digital radiography technology in China - Yingsen Pan; Feipeng Qin; Yi Shen; Ndalyolusha Tileinge Hapulile; Haoyang Zhang; Xin Ye; Shuailin Li; Xiaoming Li; Chao Yang; Xiang Zhou; Xiaoming Ying (Scientific Reports)
Abstract Extensive studies on the morphological characteristics of the coccyx, using CT or MRI techniques, have been conducted in some European and Asian countries. However, research on coccyx morphology in China remains scarce. A total of 300 subjects, who underwent sacrococcygeal digital radiological scans at the third affiliated hospital of Zhejiang Chinese Medical University between January 2022 and December 2023, were analyzed in this retrospective study. Modified coccyx morphology classification was applied. Imaging focused on the type of coccyx and the number of coccygeal segments. The subjects exhibited coccyx type III (33.3%), type II (32.7%), type I (16.7%), type IV (16%), type V (0.3%), and type VI (1%). 32 males with coccygeal type II; 76 females with coccygeal type III. Significant differences in coccyx morphology were observed between male and female (p < 0.05). Coccygeal morphology showed correlations with age (p = 0.009), body weight (p = 0.01), and BMI (p = 0.039). Among Chinese adults, type III coccyx is the most common, and the 3-segment configuration is the most prevalent. Coccyx types differ by gender, coccyx morphology is correlated with age, weight, and BMI. Our study lays the foundation for future clinical applications of these findings.